Irrigation water allocation optimization using Multi-Objective Evolutionary Algorithm (MOEA): A review - Fanuel, Ibrahim Mwita; Mushi, Allen R.; Kajunguri, Damian (EDP Sciences, 2024)
Article published by EDP Sciences in the International Journal for Simulation and Multidisciplinary Design Optimization, Volume 9, Pages A3